Um ministério com cultura: Gilberto Gil e os exercícios de antropologia aplicada - Segata, Jean; Donato, Adriana (ILUMINURAS, 2021)
Este trabalho apresenta um estudo sobre o Ministério da Cultura na gestão do Ministro Gilberto Gil e o processo de formulação das principais políticas gestadas no período 2003 a 2008. O primeiro tópico apresenta os principais mecanismos da gestão Gilberto Gil: Sistema Nacional de Cultura, reformulação da Lei Rouanet, Programa Cultura Viva – Pontos de Cultura, Plano Nacional de Cultura e Vale-Cultura. O segundo tópico faz uma reflexão sobre a relação da “ampliação do conceito de cultura” em sua dimensão antropológica e simbólica – ideia implementada pelo ministro – para novas diretrizes das políticas culturais gestadas em seu mandato. Por fim, traz uma reflexão sobre a contribuição da abertura não somente conceitual, mas também a abertura do diálogo entre diversos atores da sociedade civil neste processo de construção das novas diretrizes e das novas políticas culturais no Brasil a partir de 2003. Palavras-chave: Gilberto Gil. Cultura. Antropologia. Democratização. Políticas Públicas A ministry with culture: Gilberto Gil and the exercises in applied anthropology Abstract: This paper presents a study on the Ministry of Culture in the administration of Minister Gilberto Gil and formulating the central policies implemented from 2003 to 2008. The first topic presents the main mechanisms of the Gilberto Gil administration: the Sistema National Culture System, the reformulation of Lei Rounet, the Program Cultura Viva – Pontos de Cultura, the Plano Nacional de Cultura and the Vale-Cultura. The second topic reflects the relationship between the “expansion of the concept of culture” in its anthropological and symbolic dimension – an idea implemented by the minister – for new guidelines for cultural policies created during his term. Finally, the work reflects on the contribution of conceptual opening and the opening of dialogue between different civil society actors in this process of construction of new guidelines and new cultural policies in Brazil from 2003 onwards. It reflects on how a set of anthropological defenses to traditional, popular and ethnic knowledge, practices, and knowledge converted into an “anthropological concept of culture” guided a vision of democratizing government that is resistant to European models of culture. Keywords: Gilberto Gil; Culture; Anthropology, Democratization; Public Policies